Optimal Synthesis and Evaluation of Tri-Amine Modified Ordered Mesoporous Carbon (TriFeOMC) and Its Application for the Adsorption of Arsenic and Lead From Aqueous Solution - Khan, Hafiz Osama Sarwar; Zhu, Jianzhong; Jalil, Abdul; Sarwar, Rana Talha; Hameed, Fazli; Xu, Feifie (Frontiers in Materials, 2020)
Heavy metal pollution has become a serious problem due to increasing industrial waste, causing damage to water ecological environment, economic development and human health through their toxic effects. A unique Triamine-Iron-ordered mesoporous carbon (TriFeOMC) material was produced via a soft template approach. The ensuing sample of TriFeOMC was tested for the adsorption of arsenic (As) and Lead (Pb) along with its comparison with other two materials, which are Ordered mesoporous carbon (OMC) and Iron-ordered mesoporous carbon (FeOMC). The adsorption efficiency of TriFeOMC was excellent (92%) for the adsorption of As whereas, OMC has shown higher efficiency (88%) for the adsorption of Pb. The interaction between amino group and acidic groups on the surface of carbon formed a strong layer during Pb ions adsorption process, which resulted decreased adsorption of Pb on TriFeOMC. The Langmuir model fit for OMC, while Freundlich model fit for FeOMC. Both models fit for TriFeOMC for As whereas, Langmuir model showed comparatively better fit for Pb. The adsorption process followed an almost similar way of both pseudo models for Arsenic and Lead adsorption for OMC, FeOMC, and TriFeOMC and the adsorption process has been followed by pseudo-second-order for the adsorption of Pb. The novel material TriFeOMC with large pore volume and large surface area showed excellent results for the adsorption of arsenic from the aqueous solution. The results show the highest efficiency of TriFeOMC for adsorption of arsenic from arsenic-polluted water due to higher adsorption capacity with total pore volume 1.70 to 300.00 nm along with highly suitable pore width of 0.0680 cm3/g for adsorption, and therefore, it is highly recommended to use TriFeOMC for the adsorption of arsenic from polluted water.